Sustainability Reporting: Case of European Stock Companies - Gawęda, Adrian (European Journal of Sustainable Development, 2021)
Sustainability reporting regulations defined within NFRD (Non-Financial Reporting Directive) allow different stakeholders to assess ESG (Environmental, Social and Governance) performance of companies and their impact on people and environment. ESG data is increasingly used in strategy definition of entities, investment decision-making process and valuation of stock companies. ESG information is also reflected in ESG ratings which create comprehensive measure of ESG performance of specific entity. It outlines the need for dissemination of true and fair corporate sustainability reporting system. The main purpose of undertaken work is to evaluate the trend and evolution of sustainability reporting and ESG ratings of European listed companies in 2000-2020 period. In order to deliver results comparative analysis is used. Research proves that vast majority of European stock companies do not provide enough ESG performance which does not allow to assign them with appropriate ESG rating. Findings of analysis indicate the size of sustainability reporting accountability gap and confirm that wider group of public interest entities should be subject of NFRD.